Pengaruh Konflik Peran Ganda Terhadap Kinerja Pegawai Wanita Dengan Stres Kerja Sebagai Variabel Pemediasi Di Dinas Pendapatan Pengelolaan Keuangan Dan Aset Kabupaten Kulon Progo - Arfiena Rusinta; Harsono Harsono; Tri Maryati (Universitas Muhammadiyah Yogyakarta, 2013)
This type of research is a draft with cross sectional analytic, to know how the conflict of dual role of performance with work stress as the mediate variable. This research was conducted at the Department of Revenue Financial and Assets Management of Kulon Progo Regency. Subjects in the study were taken on the basis of a survey of women employees with criteria have been married. Engineering data collection by disseminating a questionnaire to respondents a number of 40 questionnaires, but the returns can be processed into data and research only 39 questionnaire. Data analysis in research using The Structural Equation (SEM) with data analysis tools using Partial Least Squares (PLS).The research results showed that dual role conflict to work stress. Then stress effect on work performance. The conflict also has a dual role directly to performance. The conflict also has a dual role directly to performance. Based on the results of the study also showed that work stress is able to mediate the conflict between the dual roles of performance at the Department of Revenue Financial and Assets Management of Kulon Progo Regency.